Identikasi Faktor-Faktor yang Berpengaruh pada Kualitas Air Perusahaan Daerah Air Minum (PDAM) Kabupaten Wonogiri - Abdullah Isnaini; Sarto Sarto; Agus Suwarni (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
PDAM is a local-owned institution that has the function of providing clean water services forcommunity. The company need to carry out monitoring on the quality of the water produced, either physically, bacteriologically and chemically. Good water quality positively affect the health of the users. This study was aimed to identify the factors affecting the quality of water produced by the PDAM of Wonogiri Regency, by conducting an observational study with cross sectional design. There were 16 water samples for raw water and treated water examination, and 48 water samples for house- connection water examination, i.e. consisted of 16 samples for each distance category of customers’ houses of near, moderate, and far, related to water reservoirs. The examinations were held on-site as well as at the health laboratory of the Health Office. The data analyses were using Mann-Whitney and one-way-anova tests to deter-mine the differences of water quality and Spearman-rho test to determine all relationships. All tests used significance level (?) of 0,05. The results show that: 1) in terms of bacteriological quality, by using Coliform as indicator, the differences between raw-water and treated-water, as well as between treated-water and house-connection water are statistically significant, 2) in terms of chemical quality, by using iron concentration and total hardness as indicators, the differences among raw-water, treated water, and house-connection water are not statictically significant, 3) the distance of customers’ houses were not found correlated, either with Coliform and total hardness; however, correlations were identified between the distance of customers’ houses and ironconcentration, between the distance of customers’ houses and residual chlorine, and between residual chlorine and coliform. Not all water sample has fulfilled the bacteriogical standard; however for chemical standards, either the raw-water, terated water and house-connevtion water, have met the standards.